2011
DOI: 10.1007/s00586-011-1693-x
|View full text |Cite
|
Sign up to set email alerts
|

Post atlantoaxial fusion for unilateral cleft of atlas posterior arch associated with os odontoideum: case report and technique note

Abstract: A case of a 34-year-old female with unilateral cleft of atlas posterior arch associated with os odontoideum is reported. The patient had experienced neck pain for 6 months. Five days earlier to admission the pain aggravated as a result of mild head trauma from behind. Imaging examinations revealed C1-2 subluxation as well as the deformity. After 3 days of skull traction, a sound C1-2 reduction was achieved. Post atlantoaxial fusion using bilateral transarticular screws combined with C1 laminar hook on the inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In order to increase the stability, Magerl and Seeman added transarticular C1-C2 screws, which gained wide acceptance with or without posterior laminar wiring and bone grafting. This procedure showed high fusion rates up to 100% [6,7,[16][17][18][19][20]. Although the high primary stability provided by PTS fixation meant that it was favored over sublaminar wire-based techniques, complications such as misplacement of the screws with injury to the vertebral artery and spinal cord highlight its potential risks.…”
Section: Discussionmentioning
confidence: 99%
“…In order to increase the stability, Magerl and Seeman added transarticular C1-C2 screws, which gained wide acceptance with or without posterior laminar wiring and bone grafting. This procedure showed high fusion rates up to 100% [6,7,[16][17][18][19][20]. Although the high primary stability provided by PTS fixation meant that it was favored over sublaminar wire-based techniques, complications such as misplacement of the screws with injury to the vertebral artery and spinal cord highlight its potential risks.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] The presence of OO in a setting of some segmental disorders of the spine, such as Klippel-Feil, bipartite atlas, hypertrophy of anterior arch of atlas, aplasia of the anterior arch of the atlas, split atlas, the absence of the posterior arch of the atlas, the hypertrophy of the posterior arch of the atlas, and basilar invagination have been regarded as being in favor of congenital etiology as well. 39 The last report of this kind was released in 2011 by Yang et al, 40 who presented the combination of OO with unilateral cleft of the posterior arch of atlas in a 34year-old woman. In a series of 44 patients with OO reported by Dai et al, 4 in 18 cases coexistence of OO with various congenital anomalies of the cervical spine, including Klippel-Feil syndrome, occipitalization of C1, basilar invagination, and hypertrophy of the anterior arch of the atlas, were demonstrated.…”
Section: Congenital Theorymentioning
confidence: 99%
“…34, 41 Yang et al reported the introduction of an unilateral cleft of the posterior arch of the atlas in a 34-year-old female with OO. 74 Furthermore, in acute cervical injuries, distinguishing OO from a dens fracture can be critical, as many characteristics of OO may overlap with a healed dens fracture. The smooth, well-corticated, sclerotic margins and round or oval shape as observed can help distinguish this pathological condition from non-corticated dens fractures with irregular margins of an acute type II odontoid fracture.…”
Section: Symptomatic Patientsmentioning
confidence: 99%
“…An interesting option instead of lateral mass screw is the use of C1 laminar hook under certain circumstances, where the use of lateral mass screw on one or both sides is not feasible (Figure 11). 74 …”
Section: Management Of Reducible Atlantoaxial Instability In Oomentioning
confidence: 99%
See 1 more Smart Citation